Dependency on AI Tools and Its Impact on the Knowledge Acquisition of Maritime Students in Classroom Settings: Implementing AI-Assisted Learning Enhancement Program - John Oliver F. Panes; Carol A. Abucay; Myla Christine DC. San Miguel; Zclyn V. Arpon; Lance J. Campos; Richmond A. Falmarin; MC Ruyanz E. Fisco (Future Science / FSH-PH Publications, 2026)
The integration of Artificial Intelligence (AI) tools in education has significantly transformed how students access information, complete academic tasks, and develop learning strategies. However, the increasing reliance on AI technologies raises concerns regarding its potential impact on students’ knowledge acquisition and independent learning. This study assessed the dependency on AI tools and its impact on the knowledge acquisition of maritime students in classroom settings at the Central Luzon College of Science and Technology (CELTECH), Olongapo City. The general objective of the research was to determine the level of maritime students’ dependency on AI tools and examine its relationship with their knowledge acquisition, particularly in terms of critical thinking, decision-making abilities, and study habits. Additionally, the study aimed to identify whether significant differences existed in AI dependency and knowledge acquisition when respondents were grouped according to demographic profile variables. This study employed a quantitative descriptive–correlational research design. A total of 276 maritime students from the Bachelor of Science in Marine Transportation (BSMT) and Bachelor of Science in Marine Engineering (BSMarE) programs participated in the study using stratified random sampling. Data were collected through a validated structured survey questionnaire and analyzed using statistical tools such as frequency, percentage distribution, weighted mean, Analysis of Variance, and Pearson product–moment correlation coefficient. The findings revealed that maritime students demonstrated a moderate level of dependency on AI tools and a moderate level of knowledge acquisition in classroom settings.